Problem Based Instruction Learning Model Based on Outdoor Learning Against Social Science Knowledge - Ni Kadek Sariani; I Made Suarjana; Kadek Ari Dwiarwati (Mimbar Ilmu, 2023)
Social Studies is one of the subjects taught in elementary school. However, in the implementation of social studies lessons there are still obstacles such as the learning process is still teacher-centred, this will certainly affect students' knowledge. The aim of this research is to examine the effect of using the outdoor learning-based Problem Based Instruction learning model on social studies knowledge in fifth grade elementary school. The type of research is quasi-experimental research (Quasi Experimental Design) using a nonequivalent post-test only control group design. The population involved in this research were all fifth grade elementary school students, with a total research sample of 50 students. Data collection in research was carried out using the test method, with a research instrument in the form of 25 multiple choice test questions on social studies material. The data obtained in the research was then analyzed using descriptive statistical analysis techniques and inferential statistical analysis. The results of data analysis show that the Sig. (2-tailed) of 0.000. If the value in the Sig. (2-tailed) compared with a significance value of 0.05, then the value is 0.000 < 0.05. So, this means that H1 is accepted and H0 is rejected. Based on these results, it can be concluded that the Problem Based Instruction learning model based on outdoor learning can increase the social studies knowledge of fifth grade elementary school students. 000. If the value in the Sig column. (2-tailed) compared with a significance value of 0.05, then the value is 0.000 < 0.05. So, this means that H1 is accepted and H0 is rejected.